Bariatric surgery and HIV: Joint venture between family, primary care, and HIV physicians - Ceren Aydemir; Raniah Al Saidi; Ji Soo Choi; Mohamed H. Ahmed; Dushyant Mital (Journal of Family Medicine and Primary Care)
We report a case of a 49-year-old female with a history of HIV infection for 12 years. The patient had excellent compliance with antiretroviral medications, raltegravir 400 mg twice daily and truvada once daily for HIV. Over the years, she maintained an undetectable viral load with a CD4+ count >200 cells/μL. She has a history of type II diabetes, hypertension, bipolar manic depression, endometriosis, recurrent herpes simplex attacks, arthritis in both shoulders, irritable bowel syndrome (IBS), and nonalcoholic fatty liver disease (NAFLD). She weighed 148 kg with a body mass index (BMI) of 52.08 kg/m2. Her medication included diltiazem 60 mg once a day, glyceryl trinitrate (GTN) spray, metformin 1 g twice daily, and linagliptin 500 mg once daily for her type II diabetes with glycated hemoglobin (HbA1c) of 8.4%. She has full capacity and elected to have bariatric surgery; 4 months postprocedure, she lost 28 kg with a reduced BMI of 38.62 kg/m2 with no postoperative complications. Her diabetes control improved, and she no longer required linagliptin and metformin. Following the procedure, she was given supplements including ferrous sulfate, vitamin B12, vitamin D, and calcium. She was also prescribed lansoprazole. The case illustrates that bariatric surgery is an effective and safe operation for people living with HIV. Due to complex needs and the need for regular follow-up; primary care, family, and HIV physicians can all collaborate in the care of individuals living with HIV and who underwent bariatric surgery.